Cerminan Kearifan Lokal dalam Leksikon Kerajinan Keramik pada Masyarakat Pengrajin Keramik Desa Klampok, Kabupaten Banjarnegara - Qohar, Hasan Nur Wakhidul; Fateah, Nur (Jurnal Bahasa dan Sastra, 2024)
This study examines the typical lexicon and its meanings in Banjarnegara ceramic crafts, as well as the local wisdom reflected in this tradition. The research addresses the changes in ceramic production over time, including equipment, production conditions, and socio-economic factors, which pose threats to both the craft and its associated language. Using qualitative descriptive methods, data was collected through library study, observation, and interviews with ceramic craftsmen. The study analyzes monomorphemic, polymorphemic, and word combination lexicons related to the manufacturing process, tools, materials, products, and terminology. Semantic theory is applied to uncover the meanings within the lexicon. The research identifies 47 lexicons (31 monomorphemic, 10 polymorphemic, and 6 word combinations) and reveals local wisdom values such as the ability to process natural resources and clay, patience, precision, and tenacity. This study contributes to the preservation of linguistic and cultural heritage associated with Banjarnegara ceramic crafts.